Identifikasi Kandungan Mineral (Na, K, Cl, S) Tanaman Air Kiambang (Salvinia molesta) di Waduk Batu Tegi Kecamatan Air Naningan Kabupaten Tanggamus - Irma .; Farida Fathul; Yusuf Widodo (JURNAL ILMIAH PETERNAKAN TERPADU, 2012)
Salvinia molesta is a weed reservoir Batu Tegi potential as a source of non-conventional fodder.  Information on the mineral content and its use has not been known.  This research was aimed to identification the mineral content of sodium (Na), potassium (K), chloride (Cl), and sulfur (S) to the old roots, young roots, old leaves, young leaves, and whole plant Salvinia molesta. Data were analyzed by Analysis of Variance completely randomized designed and the differences among treatments were tested by Least Significant Difference.  The results showed that in the mineral content of Na and K was present in all parts of the plant Salvinia molesta there were highly significant differences (P <0.01) while mineral Cl content on the young roots, root old, old leaves and whole plants there was no significant difference (P> 0.05).  Mineral S content on the young leaves, old roots, old leaves and whole plants was not significantly different (P> 0.05).   Keyword:  mineral, Salvinia molesta, Reservoir Batu Tegi.